2005
DOI: 10.1111/j.1365-2958.2005.05014.x
|View full text |Cite
|
Sign up to set email alerts
|

A calcium‐dependent protein kinase regulates Plasmodium ookinete access to the midgut epithelial cell

Abstract: SummaryPlasmodium parasites are fertilized in the mosquito midgut and develop into motile zygotes, called ookinetes, which invade the midgut epithelium. Here we show that a calcium-dependent protein kinase, CDPK3, of the rodent malarial parasite ( Plasmodium berghei ) is produced in the ookinete stage and has a critical role in parasite transmission to the mosquito vector. Targeted disruption of the CDPK3 gene decreased ookinete ability to infect the mosquito midgut by nearly two orders of magnitude. Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
187
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(201 citation statements)
references
References 28 publications
8
187
1
2
Order By: Relevance
“…Also, the activity of CDPK3 is required for P . berghei ookinete motility and engagement with the mosquito midgut epithelium (Ishino et al ., 2006; Siden‐Kiamos et al ., 2006), suggesting that besides cGMP, Ca 2+ is important for ookinete motility. In accord with these findings, quantitative phosphoproteomics comparing P .…”
Section: The Zygote‐to‐ookinete Conversionmentioning
confidence: 99%
“…Also, the activity of CDPK3 is required for P . berghei ookinete motility and engagement with the mosquito midgut epithelium (Ishino et al ., 2006; Siden‐Kiamos et al ., 2006), suggesting that besides cGMP, Ca 2+ is important for ookinete motility. In accord with these findings, quantitative phosphoproteomics comparing P .…”
Section: The Zygote‐to‐ookinete Conversionmentioning
confidence: 99%
“…We synthesized a compound library based upon a known specific inhibitor (BIX-01294) of the human G9a histone methyltransferase. Two compounds, BIX-01294 and its derivative TM2-115, inhibited P. falciparum 3D7 parasites in culture with IC 50 values of ∼100 nM, values at least 22-fold more potent than their apparent IC 50 toward two human cell lines and one mouse cell line. These compounds irreversibly arrested parasite growth at all stages of the intraerythrocytic life cycle.…”
mentioning
confidence: 99%
“…The initial steps of sporogony following fertilisation in P. berghei require Pbnek-4, a NIMA-related kinase with a role in meiosis (Reininger et al, 2005), and a second enzyme of this family was recently shown to also be essential for meiosis in both P. berghei and P. falciparum (Reininger et al, 2009). PbCDPK3 is required for traversal of the mosquito midgut epithelium (Ishino et al, 2006;SidenKiamos et al, 2006). In summary: i) Plasmodium PKs are divergent from their human counterparts, and it is difficult to reconstruct signalling pathways from sequence databases, ii) a collection of parasite clones lacking specific kinases has been constituted and is growing (in both P. berghei and P. falciparum), allowing the study of phenotypes mostly in sexual development/sporogony, iii) some PKs have been demonstrated to be essential for the asexual cycle, and iv) several recombinant PKs are available for biochemical studies and drug discovery activities.…”
Section: Protein Kinases (Pks)mentioning
confidence: 99%
“…The protein kinases CDPK4 and Pbmap-2 have been associated with the production of male gametes (Billker et al, 2004;Khan et al, 2005;Rangarajan et al, 2005), Pbnek-4 and Pbnek-2 with ookinete maturation (Reininger et al, 2005;Reininger et al, 2009), and PbCDPK3 and guanylate cyclise beta with ookinete physiology (Ishino et al, 2006;SidenKiamos et al, 2006;Hirai et al, 2006). The role of signalling molecules in several other phases of sexual differentiation is however completely unknown, despite the fact that some of these processes, such as the establishment of the gametocyte parasitophorous vacuole, or gamete emergence are intrinsically complex cellular rearrangements, which proceed in response to specific cellular and environmental signals.…”
Section: A B Sexual Developmentmentioning
confidence: 99%